Medicago spp. as potential sources of bioactive isoflavones: Characterization according to phylogenetic and phenologic factors - Barreira, João C.M. (2018)
A high variety of plant species are often proposed as potential natural sources of specific bioactive components, with emphasis in phenolic compounds. However, the ability to produce a determined phytochemical might be variable, even among species with close phylogeny. Furthermore, the metabolic dynamics vary greatly according to phenologic factors. Herein, it was verified whether isoflavone production in Medicago spp. is more associated with phylogenetic or phenologic determinants, to define the optimal productive conditions. Isoflavone profiles were characterized in field-grown Medicago species in three phenologic stages. Isoflavones were extracted by matrix solid-phase dispersion method and analyzed using high-performance liquid chromatography coupled with a diode-array detector. The obtained data were evaluated by a generalized linear model (GLM) and linear discriminant analysis (LDA). Formononetin, genistein and irilone were the most abundant isoflavones, reaching values higher than those present in acknowledged plant sources like soy or red clover. Outputs from GLM and LDA indicate that the phylogenetic factors are the most defining criteria. This study promotes Medicago spp. as potential isoflavone sources, particularly because the effects of these compounds are highly dependent on their type and concentration, with potential application as foodstuff, feedstuff, or in the nutraceutical and pharmaceutica l industry.